Model Comparison of The Floating Foundations for The Development of Floating Houses at Coastal Areas - Son Haji; Henny Pratiwi Adi; Moch Faiqun Ni’am (UNISSULA Semarang, 2018)
ABSTRACT Floating house is a building, which stands or floats on water by relying itself on the weight and the area sunk as the load parameter compatible to the structure. This house can float or be placed on the seashore on the water. This research was conducted by comparing the magnitude of the floating force (Fa) of the three foundation materials of the houses, namely plastic drum, Styrofoam and bamboo. The materials were calculated based on the total load of the house (G), with the safety number of 1.5. .The research result is the total load of the floating house structure (G) is 364.585,5 Newton (down), the floating force (Fa) magnitude of plastic drum as the foundation material is 549,814 Newton (upward), Styrofoam as the foundation material is 552,720 Newton (upward), and Bamboo as the foundation material is 540,883 Newton (upward). The amounts of the foundation materials for plastic drum are 232 pieces, for Styrofoam are 56 sheets, and for bamboo are 3900 sticks. Keywords: Floating house, floating foundation, floating force, plastic drum, Styrofoam, bamboo